Round Table- Gwangju Biennale 2012 - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2012)
Nancy Adjania; CAMP; Sheba Chhachi; Fouad Elkoury; Maha Mamoun; Ala Younis; Wassan Al Khudairi; Sophia Al Maria; Faycal Baghriche; Joana Hadgithomas and Khalil Joreige; Shuruq Harb; Malak Helmy; Nasrin Tabatabai and Babak Afrassiabi, PAGES; Wael Shawky; Slavs and Tatars; Xurban Collective; Mami Kataoka; Haroon Mirza; Sunjung Kim; Abraham Cruzvillegas; Jenny Holzer; Michael Joo, Kim Beom; Carol Yinghua Lu; Andy Hope; Rasheed Araeen; Boris Groys; Alia Swastika; Anri Sala; Vertical Submarine
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions